CRISPR-based point-of-care diagnostics for viral hepatitis: from molecular design to clinical implementation - Lanke Lin; Fukang Luo; Shan Liu; Xianli Tong; Xuyu Xu; Weijia Yi; Xinyue Deng; Hongzhi Luo (Frontiers in Bioengineering and Biotechnology, 2026)
Timely etiological diagnosis of viral hepatitis is essential for surveillance, treatment initiation, linkage to care, and elimination efforts. In resource-limited settings, however, diagnostic pathways are frequently disrupted by centralized nucleic acid testing, specimen-transport requirements, delayed reporting, and loss to follow-up. CRISPR-Cas-based point-of-care testing may help shorten these pathways, but its clinical value cannot be judged by analytical sensitivity alone. This review evaluates CRISPR-Cas strategies for detecting hepatitis A, B, C, D, and E viruses by linking molecular design to virus-specific clinical and public-health decisions. We compare target selection, Cas effectors, amplification strategies, readout formats, specimen processing, genotype coverage, clinical validation, and implementation feasibility. For each virus, the evidence is evaluated in relation to the principal diagnostic need, the potential contribution of CRISPR-Cas, the maturity of the available evidence, and the remaining requirements for deployment. Current evidence is most advanced for HBV and HCV, whereas HAV, HDV, and HEV applications remain less developed or more context dependent. Future platforms should prioritize clinically meaningful detection thresholds, closed-tube sample-to-answer workflows, internal controls, genotype-diverse validation, reagent stability, non-expert usability, and transparent pathway-level cost evaluation.